Analisis Pemelajaran Kolaborasi Guru Di Masa Pandemi Covid-19 Pada Siswa Kelas III A Di SDN 004 Samarinda Utara Tahun Pembelajaran 2020/2021 - Yustika; Afdal; Tunru, Andi Alif (SISTEMA: Jurnal Pendidikan, 2021)
This reasearch is based on the importance of the collaboration bentween parents and teachers during covid-19 pandemic. The aims of this research is to analyze the collaboration between parents and teacher in accommodate learning process during covid-19 pandemic on the 3rd graders of SDN 004 Samarinda Utara Academic Year 2020/2021. The technic used to determined the subject is purposive sampling and the technic used to analyze the data is data collection, data selection, data presentation, and drawing conclusions. The type of triangulation used is source triangulation. The result of the research which formed by extending communication through WhatsApp Application and collaborate in learning activities and students’ development while students learning from home. During pandemic, teachers conducted the learning process through some remote learning application, but its difficult for many parents who did not know how to use the remote learning applications, therefore they use whatsApp application whish found easier to use.